Digitalisasi Kawasan Desa Tambak Lekok, Jati Rejo, dan Tampung Melalui Pemetaan Digital Pada Aplikasi Google Maps - Bayhaqi, Hasmi Nur; Karunia, Ardica; Rachmadhani Muchtar, Nabilah; Dzinnur, Cilda Thesisa Ilmawan; Darmawan, Didit; Hariani, Mila; Hardyansah, Rommy (PT Ininnawa Paramacitra Edu, 2024)
Villages throughout Indonesia, such as Tambak Lekok, Jatirejo, and Tampung, have abundant natural potential and human resources, which, if utilized well, can improve the welfare of the local population. However, even though this potential is large, it is often not explored optimally due to various obstacles, including limited basic infrastructure such as roads, electricity and clean water. Apart from that, accessibility to information, which is very crucial in the digital era, is still limited in many villages. Digital mapping offers an important solution in overcoming this obstacle, because through this technology, village communities can more easily access relevant information about their area, which was previously difficult to reach due to limited infrastructure and technology. Through digital mapping, detailed information regarding the location of various public facilities such as schools, health centers, places of worship and markets can be accessed quickly and accurately. The implementation of digital mapping in villages such as Tambak Lekok, Jatirejo, and Tampung via the Google Maps application has proven to be an effective initiative in maximizing local potential and encouraging sustainable development. This project not only increases the accessibility and visibility of the village, but also introduces digital technology to the community, thereby strengthening their involvement in the development process. With the Asset-Based Community Development (ABCD) approach, local village assets have been successfully mapped and promoted to a wider audience, opening up new opportunities in the economic, tourism and public service sectors. This approach allows villages to more optimally utilize their resources and benefit from greater involvement in markets and information networks.